Defining and Defending the Middle Ages with C. S. Lewis - Brian Murdoch (Humanities, 2020)
The scholarly writings of C. S. Lewis (1898–1963) have both inspired the study of the Middle Ages and confirmed the relevance to the humanities that medieval literary texts can have for the present. He was aware that the straitjacket implied by periodisation can blind us to the universal values presented in medieval literature. Qualitative assumptions made about the (usually undefined) Middle Ages include an alienating remoteness, and also a general ignorance, especially of science and technology. Lewis drew attention to the knowledge of astronomy, for example, and pointed out that medieval technical skills in architecture, agriculture and medicine are important for us to be aware about. Three medieval works illustrate this universality with respect to technical skills (the Völundarkviða); identity and the self (the Hildebrandslied); and the popular love-song (the courtly love-lyric). Lewis cautioned against pejorative terms like ‘Dark Ages’, noted problems of perspective in assessing all pre-modern literature, and showed that earlier works have a continuing value and relevance.